Designing a trifunctional hydroxyapatite based nanocapsule with bone targeting properties - Cho, Xing Ling. (2011)
Hydroxyapatite (HA) and Bisphosphonate (BP) are well known for their close resemblances to natural bone and have been widely used in medical treatments for bone deprivation diseases for many years. As such, a hybrid model encompassing the qualities of both HA and BP would serve as a promising tool for effective drug delivery with specific bone targeting. In this project, a new methodological approach via surface silanisation chemistry was proposed to construct such hybrid material.